The Third Way and beyond Criticisms, futures and alternatives - Hale, Sarah; Leggett, Will; Martell, Luke (Manchester University Press, 2004)
The Third Way is said to be the guiding philosophy for New Labour and centre-left parties and governments across the globe. Moving beyond attempts to define and defend the Third Way, this innovative collection embarks on a critical examination of this key concept. The editors draw on expert contributions from a range of disciplines and perspectives to dissect the Third Way in theory and in practice, assess its legacy and suggest alternatives. The book begins by reviewing attempts to define the Third Way. It then examines what the Third Way implies for our understanding of the economy and the state, before critically addressing the philosophical and practical implications of its attempt to use the term 'community'. The final section deconstructs Third Way rhetoric and discourse. The conclusion reviews how these critical insights might form a basis for alternative political projects. Written in a rigorous but accessible style, this interdisciplinary collection is essential reading for anyone with an interest in understanding a key idea propounded by New Labour and the contemporary centre-left. It will appeal to anyone studying politics, sociology, contemporary history, social policy, social and political theory, and applied philosophy. It provides both an introduction to the topic and new and original insights for specialists in the area.